Pickleballers - Long, Ilana (Berkley Romance, 2024)
"A pickleball newbie looking to recover from life's swings and misses crosses paddles with love in this debut romantic comedy. Meg Bloomberg is in a pickle. When Meg's ex turns out to be a total dink, her bestie suggests a mood-lifting pickleball excursion to Bainbridge Island. It's supposed to be an easy lob, a way to heal-not the opening serve to a new courtside romance that's doomed to spin out. But no matter how Meg tries, she can't shake her feelings for Ethan Fine. A charismatic environmental consultant and Bainbridge local, Ethan is eager to play with her on-and off-the court. But when Meg discovers that Ethan's pickleball promises are not the real dill, she decides the match is over. It's time for Meg to take control of her own game. And maybe, just maybe...love will bounce back"--